2023
DOI: 10.3390/insects14030266
|View full text |Cite
|
Sign up to set email alerts
|

Physical Properties of Substrates as a Driver for Hermetia illucens (L.) (Diptera: Stratiomyidae) Larvae Growth

Abstract: The growth and nutritional profile of the black soldier fly larvae (BSFL) is usually investigated and compared when the larvae feed on substrates that differ in the chemical composition as well as physical properties. This study compares BSFL growth on substrates that differ primarily in physical properties. This was achieved by using various fibres in the substrates. In the first experiment, two substrates with 20% or 14% chicken feed were mixed with three fibres (cellulose, lignocellulose, or straw). In the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 48 publications
2
12
0
Order By: Relevance
“…The performance of larvae could be influenced by the aeration within the substrate which in turn depends on the stickiness [21], viscosity [77], particle size [28,78], and physical properties of the feed, such as its fibrous nature [79]. The particle size range described in the literature includes 0.1-1.5 mm [75], ~0.4 mm [33], ≤1-15 mm [80], ~1 mm [63], ~5 mm [81], 4.00-6.35 mm [78], 1-2 cm [23], and ≤3.8 cm [82]. According to Dortmans et al (2017), the substrate has to be shredded to a particle size of at least less than 1-2 cm in diameter [23].…”
Section: Substrate Aerationmentioning
confidence: 99%
See 2 more Smart Citations
“…The performance of larvae could be influenced by the aeration within the substrate which in turn depends on the stickiness [21], viscosity [77], particle size [28,78], and physical properties of the feed, such as its fibrous nature [79]. The particle size range described in the literature includes 0.1-1.5 mm [75], ~0.4 mm [33], ≤1-15 mm [80], ~1 mm [63], ~5 mm [81], 4.00-6.35 mm [78], 1-2 cm [23], and ≤3.8 cm [82]. According to Dortmans et al (2017), the substrate has to be shredded to a particle size of at least less than 1-2 cm in diameter [23].…”
Section: Substrate Aerationmentioning
confidence: 99%
“…The authors explain that the increased access of the feed to microbes and reduced oxygen transport are assumed to be reasons for lower larval weight with a smaller particle size [78]. Yakti et al (2023) found that the larval weight reduced from ~125 mg FM to ~75 mg FM as the straw particle size decreased from >3 mm to ≤1 mm [80]. Usage of a blended substrate could result in less accessibility of feed for the larvae due to high feed compactness and lower oxygen levels at the bottom of the rearing box forming anaerobic zones harboring corresponding microbiota [61].…”
Section: Substrate Aerationmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study the in uence of the substrate moisture content on BSFL rearing is investigated. The moisture content of the substrate is pivotal as larval performance, e.g., growth, bioconversion e ciency, waste reduction and survival, is highly affected by the substrate moisture content (Bekker et Yakti et al, 2023). Understanding the in uence of substrate moisture content on the rearing process is therefore crucial for the optimization of BSFL rearing.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the in uence of substrate moisture content on the rearing process is therefore crucial for the optimization of BSFL rearing. Studies have shown that substrate moisture content is positively correlated to larval growth, however when substrate moisture contents are too high, survival drop signi cantly, often leading to inconsistencies in yield per box [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%